2022
DOI: 10.1101/2022.06.21.497047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Within-host evolutionary dynamics and tissue compartmentalization during acute SARS-CoV-2 infection

Abstract: The global evolution of SARS-CoV-2 depends in part upon the evolutionary dynamics within individual hosts with varying immune histories. To characterize the within-host evolution of acute SARS-CoV-2 infection, we deep sequenced saliva and nasal samples collected daily from immune and unvaccinated individuals early during infection. We show that longitudinal sampling facilitates high-confidence genetic variant detection and reveals evolutionary dynamics missed by less-frequent sampling strategies. Within-host d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…For deepening the knowledge of the evolutionary process of in-host DAA evasion and the resulting impact on druggability, we further propose continuous time-resolved sequencing of SARS-CoV-2 samples collected from COVID-19 patients, who are treated with protease inhibitors, during their treatment phase. Similar studies, but with untreated patients, have recently been reported 71,72 . Finally, we propose the expression of the newly evolved M pro variants for inhibition experiments and subsequent determination of their experimental structural complexes.…”
Section: A Call For Further Characterization Of Emerging M Pro Variantssupporting
confidence: 78%
“…For deepening the knowledge of the evolutionary process of in-host DAA evasion and the resulting impact on druggability, we further propose continuous time-resolved sequencing of SARS-CoV-2 samples collected from COVID-19 patients, who are treated with protease inhibitors, during their treatment phase. Similar studies, but with untreated patients, have recently been reported 71,72 . Finally, we propose the expression of the newly evolved M pro variants for inhibition experiments and subsequent determination of their experimental structural complexes.…”
Section: A Call For Further Characterization Of Emerging M Pro Variantssupporting
confidence: 78%
“…However, we found that all transmission pairs had equal bottlenecks even when we tested mutually exclusive transmission pairs. Second, virus populations may be spatially segregated within hosts, and the transmitted population may not have been well sampled by our analysis of nasal swabs [43][44][45][46][47] . However, given the low viral diversity identified in nearly all cases, even spatially segregated viral populations are likely to be genetically similar to each other.…”
Section: Discussionmentioning
confidence: 99%
“…These include a quantitative model of the in-host evolutionary dynamics of coronaviruses under the pressure of a targeted antiviral drug, accompanied by structural-bioinformatic studies of M pro variants in complex with its natural substrate and inhibitors. Evolutionary studies with remdesivir-treated ( 71 ) and untreated ( 72 , 73 ) patients have recently been reported. For deepening the knowledge of the evolutionary process of in-host DAA evasion and the resulting impact on druggability, we further propose continuous time-resolved sequencing of SARS-CoV-2 samples collected from COVID-19 patients, who are treated with protease inhibitors, during their treatment phase.…”
Section: Discussionmentioning
confidence: 99%